Assessment of Family Caregiver Burden and Its Relationships Between Quality of Life, Arm Disability, Grip Strength, and Lymphedema Symptoms in Women with Postmastectomy Lymphedema: A Prospective Cross-Sectional Study - AKYÜZ, GÜLSEREN DERYA (AVES, 2019)
Objective: the aim the study is to assess relationships between caregiver burden, quality of life, arm disability, grip strength, and lymphedema symptoms in women with post mastectomy lymphedema. Materials and Methods: Fifty-two patients with postmattecromy lymphedema were recruited. Burden Interview, Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire and European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire (EORTC QLQ-30 and EORTC QLQ BRE-23) were used for the assessments of caregiver burden, arm disability, and quality of life. Lymphedema symptoms were questioned by Visual Analogue Scale (VAS) for pain, heaviness, and tension. Grip strength and arts volumes of the affected and unaffected sides were measured. Results: Statistically significant positive correlations were detected between Burden Interview scores and DASH scores, VAS for pain and EORTC QLO-30 symptom scores. There were statistically negative correlations between Burden Interview and grip strength of affected side and unaffected side and lymphedema duration. Multiple linear regression was calculated to predict Burden Interview and EORTC QLO-30 functional and symptom scores based on age, DASH, stage, and duration of lymphedema. DASH score was significant predictors of Burden Interview while DASH score and Burden Interview scores were significant predictors of quality of life. Conclusion: Arm disability indicates caregiver burden and quality of life in patients with posrmastectomy lymphedema while caregiver burden predicts the quality of life. These findings have implications for the management of lymphedema We suggest that arm disability should be diagnosed and treated to improve caregiver burden and quality of life.
Keywords: Breast cancer; caregiver burden; disability; lymphedema; quality of life; BREAST-CANCER; IMPACT